Cinema e contraluz: limiares da repressão na cultura midiática argentina - Márcio Serelle (Galáxia (São Paulo), 2014)
This paper examines the backlighting technique used in Argentine movies (mainly Valentín, Kamchatka, and The Secret in Their Eyes), seen as a kind of narrative composition in which events related to dictatorships and other forms of repression operate in the dark, but strongly affect the fate of the characters. Starting from a brief overview of the internationalization of the Argentine film industry, which, as early as the mid-1980s, had already articulated conventional dramatic structures and political denunciation, this study analyzes how part of the cinema of this century represents the violence of authoritarian states. Be it through imaginative investment, metalanguage, or allegory, these narratives renounce graphic images of the violence of repressive apparatuses and create dramaturgical compositions of highly effective communication. Thus, this work discusses the reflective capacity of these films as it pertains to the relationship between the fictional, mediatic and social contexts.